The nest, eggs, and nestlings of the Rufous-naped Brush-finch (Atlapetes latinuchus latinuchus) in southeastern Ecuador: El nido, huevos, y pichones del matorralero nuquirrufo (Atlapetes latinuchus latinuchus) en el sureste de Ecuador (Ornitología Colombiana, 2021)
I describe observations at two nests of the Rufous-naped Brush-Finch (Atlapetes latinuchus) from the eastern Andes of southern Ecuador. Due largely to confusion in taxonomy and recent shifts in taxonomic affinities within the group, there has been some confusion as to nest descriptions for this widely distributed Andean genus. Although the eggs of this species have been previously described, this is the first time that the nest of the nominate subspecies has been described. Two nests of A. l. latinuchus were open cups similar to those of other species of Atlapetes; both were built near the ground in areas of disturbance. One nest took around 9 days to build, and at one nest the incubation period was 16 days and nestlings fledged after 15 days.